(untitled) (Journal of Civil Engineering Researchers, 2024)
Due to the important role that bridges play in rescue operations after an earthquake, it is necessary that these structures have a higher level of protection against seismic attacks. Earthquake identifies the weak points of the structure and causes the most damage there. Bridges are very vulnerable to these attacks due to their low degree of uncertainty. All bridges built before 1971 were designed with the elastic design method (permissible stress). In this method, the effects of plasticity, section cracking, and plastic deformation are not taken into account. The change of seismic locations based on the principles of elastic design is much less. It is because the structure experiences in a real earthquake, one of the consequences of which is the falling of the decks due to the loss of the support surface. The decision to strengthen the bridge was made when there were many bending and shear cracks on the king beams. The bridge was created. The use of FRP profiles can significantly prevent the damage caused by corrosion and is a good alternative to the traditional methods of strengthening the structure. In this study, a design for the deck of a steel bridge with I beams is presented. The shape of reinforcement using FRP fibers with vinyl ester resins has also been investigated, the effect of the geometry of FRP profiles has been investigated. The presented specifications are optimized to obtain a lasting shape and section, especially for the pultrusion process. FRP materials are light, resistant to corrosion and have high tensile strength. These materials come in different forms and range from multi-layer factory sheets to dry sheets that can be twisted on various structural forms before adding resin, is available. The durability and high tensile strength of FRP materials are among the advantages of these materials. The durability and long-term performance of FRP requires more research, which is ongoing and continues.